Witalizm kobiecy. Mapa problemów, sieć tradycji - Legeżyńska, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Vitalism is a vague and ambiguous philosophical notion which researchers try to apply to describe modernist literature, especially from the period of the Young Poland. The author of the article suggests that vitalism should be approached as an interpretive category. She examines whether it is possible to distinguish feminine vitalism and conducts an analysis of selected types of literature (H. Poświatowska, A. Świrszczyńska, W. Szymborska, A. Szymańska, U. Kozioł, M. B. Kielar). The analysis shows that modernist feminine vitalism in the poetry of the second half of the 20th century encompasses various types of affirmations: of nature, corporeality and existence. In late modernity it transforms into post-vitalism, which signifies new understanding of life and the reduction of the anthropocentric perspective, both determined by new discoveries of science.